PENGARUH KONSENTRASI GIBBERELLIC ACID (GA3) TERHADAP PERKECAMBAHAN BENIH AREN (Arenga pinnata Merr.) - Matanari, Jawaller; Gusriani, Yunda; Manullang, Benget H (LPPM Universitas Katolik Santo Thomas Medan, 2023)
This study aims to determine the effect of the concentration of gibberellins acid growth regulator (GA3) on the germination of sugar palm seeds. The experiment was carried out at Graha Tanjung Anom with an altitude of about 50 masl from December 2021 to May 2022. The experiment was carried out using a non-factorial Randomized Block Design. The factors studied were the treatment of gibberellins acid concentrations with 8 levels namely G0 ; zero or no gibberellins acid, G1 : 0.5 mg / l ; G2 : 1.0 mg/l ; G3 :1.5 mg/l : G4 :2.0 mg/l : G5 : 2.5 mg/l ; G5 ; 2.5 mg/l ; G6 ; 3.0 mg/l and G7 ; 3.5mg/l. The treatment consisted of 3 repetitions (blocks) so that there were 3x8 = 24 experimental units (plots). Each experimental unit (plot) consisted of 20 seeds (polybags). Parameters observed were the percentage of seeds germinating, average germination age, seedling height, number of leaves and stem diameter. Based on data analysis (Anova), and the discussion some conclusions can be drawn as follows; Concentrations of 0 to 3.5 mg/l GA3 markedly increased the percentage of seed germination, accelerated the germination age of 5.48 days, tended to increase seedling height and number of leaves as well as the diameter of the base of the seedling stems. It is necessary to investigate the effect of GA3 concentration and soaking time on sugar palm seed germination.